2021
DOI: 10.1038/s41598-021-00130-y
|View full text |Cite
|
Sign up to set email alerts
|

Increasing urinary podocyte mRNA excretion and progressive podocyte loss in kidney contribute to the high risk of long-term renal disease caused by preterm birth

Abstract: Podocyte abnormalities are common mechanism driving the progression of glomerular diseases, which account for most chronic kidney diseases (CKDs). However, the role of podocyte in the mechanism of high-risk long-term CKD caused by prematurity has not been well clarified. In present study, urine samples of 86 preterm infants and 32 full-term infants were collected, and podocyte-specific podocin mRNA levels in urine pellet were applied to indicate urinary podocyte mRNA excretion. In addition, in a preterm animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Studies have shown that glomerular and tubular changes are strongly associated with the pathogenesis of DKD 24,25 . In line with this finding, podocyte and tubule biomarkers may predict the onset or progression of DKD [18][19][20] . Furthermore, accumulated evidence has demonstrated that urinary podocytes and tubular proteins can be positively correlated with hyperglycemia 26,27 , and interestingly, these levels are elevated even in normoalbuminuric patients with diabetes 25,28 .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Studies have shown that glomerular and tubular changes are strongly associated with the pathogenesis of DKD 24,25 . In line with this finding, podocyte and tubule biomarkers may predict the onset or progression of DKD [18][19][20] . Furthermore, accumulated evidence has demonstrated that urinary podocytes and tubular proteins can be positively correlated with hyperglycemia 26,27 , and interestingly, these levels are elevated even in normoalbuminuric patients with diabetes 25,28 .…”
Section: Discussionsupporting
confidence: 70%
“…Herein, we revealed the nephroprotective action of AFA extract adjuvant to insulin, as indicated by the maintenance of baseline expression levels of mRNA (Nphs1, Nphs2, Wt1, and Lrp2) and protein (nephrin, podocin, WT1, and megalin) in the kidney tissue. Interestingly, nephroprotection was also evidenced through the www.nature.com/scientificreports/ reduction of urinary loss of nephrin, podocin, WT1, and megalin, given that these proteins are markers of kidney glomerular and tubular integrity, and their loss is typically associated with the onset of kidney dysfunction [18][19][20] . Nephrin and podocin are slit diaphragm-associated proteins involved in the maintenance of the glomerular filtration barrier.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the hypothesis of lower nephron numbers, our recent study [ 19 ] also put forward the involvement of the podocyte depletion hypothesis [ 20 23 ]. In that study, a preterm rat model was established by delivery 2 days early.…”
Section: Introductionmentioning
confidence: 99%
“…Although that study identified the role of podocyte loss caused by preterm birth in long-term CKD in animal studies, there are many differences between preterm rats and preterm infants because preterm infants experience a much more complex disease process, such as asphyxia, infection, oxygen therapy, drug exposure, and various maternal factors. Podocyte loss in preterm infants has rarely been reported [ 19 , 24 ]. In addition, it is also unclear which perinatal factors affect podocyte loss.…”
Section: Introductionmentioning
confidence: 99%
“…Creatinine (reiged diagnostic kit) [14] Creatinine level measurements were done using Reiged Diagnostic Kit. The kit included R1, R2, and creatinine 2 mg/dL standard solutions.…”
Section: Acute Toxicity Test [13]mentioning
confidence: 99%